Dinamika Hara dan Produksi Lateks Tanaman Karet dengan Pemupukan dan Pemberian Stimulan pada Ultisols - Bakri Bakri; Agus Hermawan; Rahmawati Rahmawati (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Bakri B, Agus H, Rahwamati R. 2020. The dynamics nutrient and production of rubber plant latex with fertilization and stimulant on ultisols. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xxx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The purpose of this research was to determine effect of fertilization stimulants on nutrient availability and the production of rubber latex on Ultisols. This research was conducted on May 2020 in rubber gardens public, Sungai Lilin km.114, Musi Banyuasin, South Sumatera.This research used Randomized Complete Block Design with 2 factors those were first factor was fertilizer and second factor was stimulants. The fertilizer consists of 4 levels, namely (without fertilizer and N, P, K fertilizer) and stimulants of 4 levels, namely (without stimulan, stimulant A, and stimulants B) and repeated 3 replication, so that 18 units of experiments were obtained. Each experiment consists of 5 plants so that the total number of plants as many as 90 plants. The results of this study showed that the stimulants did affect the yield of rubber plants. There is interaction of the experiment N, P, K fertilizer and stimulan A P1 S 1to production of rubber latex.